2014
DOI: 10.1017/s0950268814002398
|View full text |Cite
|
Sign up to set email alerts
|

The status of tularemia in Europe in a one-health context: a review

Abstract: SUMMARYThe bacterium Francisella tularensis causes the vector-borne zoonotic disease tularemia, and may infect a wide range of hosts including invertebrates, mammals and birds. Transmission to humans occurs through contact with infected animals or contaminated environments, or through arthropod vectors. Tularemia has a broad geographical distribution, and there is evidence which suggests local emergence or re-emergence of this disease in Europe. This review was developed to provide an update on the geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 115 publications
(149 reference statements)
2
144
1
5
Order By: Relevance
“…24 The clinical manifestation may range from asymptomatic infection to septic shock and death. 25 Signs and symptoms include: a skin ulcer that forms at the site of infection -usually a small lesion, a painful regional lymphadenopathy, fatigue, weight loss, fever, chills, myalgia, joint pain, diarrhea. 4 In our study, medical history and clinical presentation were typical for ulceroglandular form of tularemia.…”
Section: Discussionmentioning
confidence: 99%
“…24 The clinical manifestation may range from asymptomatic infection to septic shock and death. 25 Signs and symptoms include: a skin ulcer that forms at the site of infection -usually a small lesion, a painful regional lymphadenopathy, fatigue, weight loss, fever, chills, myalgia, joint pain, diarrhea. 4 In our study, medical history and clinical presentation were typical for ulceroglandular form of tularemia.…”
Section: Discussionmentioning
confidence: 99%
“…Ftt is readily found in the environment as both a free-living and arthropodtransmitted pathogen [5,6]. Thus, this bacterium also represents a persistent public health threat in both developed and underdeveloped areas of the world [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The common vole has been implicated in the spillover to other species and in the enzootic maintenance of the bacteria (World Health Organization 2007, Rossow et al 2014, Hestvik et al 2015. A study in Ukraine also identified long-standing foci of F. tularensis associated with the common vole and Dermacentor spp., among other species (Hightower et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent outbreaks and an increasing incidence in parts of Europe (Hestvik et al 2015), the ecology of F. tularensis is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%